Reforms — Not revolutionary changes - Hans-Jürgen Wischnewski (Intereconomics, 1967)
Development aid is rightly considered to be one of the most important tasks of our time. Irrespective of whether this aid is seen from the political, economic or simply from the humanitarian aspect, there is no question of its urgency and of its broad field of application. On the other hand, there, is very little agreement in donor and recipient countries about the adequate volume of development aid, the methods of raising it and the forms of distribution. But in view of the enormous magnitude and the diversity of range of this task, it would be a mistake to resign or—panic-stricken—to wish to achieve too much too soon. What donor countries can and must do is to plan aid within the limits of their possibilities and in accordance with the circumstances of developing countries and be resolute in its execution. The following interview shall help to clarify the principles and forms of West Germany's development aid, as well as improvements in its effective implementation.
Keywords: 330; Interview